Playing School: female elementary school teachers' stories of childhood games and post-feminist tomorrows - Sally Campbell Galman; Christine Mallozzi (Universidade Federal do Rio Grande do Sul, 2020)
Not only do many little girls in the United States and elsewhere play school, but when they grow up, they sometimes become teachers, at which point the story of playing school takes on a new narrative and discursive function. Using narrative and performance theories, and discourse analysis, we analyze stories about playing school told as part of a multi-site qualitative study of new and pre-service American elementary teachers' life histories. We examined these narratives with one eye on pop culture and mid to late 1990s girlhood, and the other on the use to which the game of playing school is put both discursively and in practice. Implications for teacher preparation and professional identity, as well as the gendered face of teachers' work, conclude the paper.